Os/AS professores/as e o futuro à educação - Dalla Valle, Paulo Roberto; de Lima Ferreira, Jacques (Retratos da Escola, 2024)
The aim of this article is to present a review of the book Professores: libertar o futuro by Professor António Nóvoa with the collaboration of Professor Dr. Yara Alvim. Published in Brazil in 2023, the ten texts that make up the book reflect on contemporary issues in the school context, highlighting the appreciation and defense of public schools, teachers, their training and the future of education, bringing up contextualizations and demands of the present reality, the unfolding of the Covid-19 Pandemic and its relationship with the direction of education. The ten texts in the book, including some previously unpublished and others already published, underline the role and importance of teachers in thinking about and confronting the necessary transformations, given the demands and direction of education. Dedicated to those who believe in teachers and public schools, the book bridges the gap between the past and the futures that lie ahead, based on rigorous reflections and contextualizations of the themes defined by Unesco and the Labour Organization for World Teachers' Day in recent years, as well as, based on Unesco's 2021 report, "Reimagining our futures together: a new social contract for education". Theoretical and reflective discussions that circumscribe contemporary educational reality stand out, such as: the role of teachers and the futures of education, the centrality and recognition of the teacher in the teaching and learning process, the need for teachers' freedom as the beginning and end of their profession, professional knowledge, professionality, the teaching profession, the future of the profession after the pandemic articulated with the need for its reinvention, empowering and broadening the role of teachers and their training as liberating and transforming dimensions, from a third training space - professional knowledge - conceived as a common house, a space for permanent and collective construction of the profession because it involves different organizational and collaborative dimensions, broadening the possibility of liberating the future because this movement begins in and with teachers.